(untitled) (Research, Society and Development, 2022)
This article aims to describe the importance of reverse logistics, in particular that of glass, through an applied survey with 158 respondents, allowing to present a scenario on the topic addressed and also the relevance of disseminating this theme, where it is also presented the solid waste law of 2010 so that readers can have a better understanding and practice preventive actions. The research identified that there are gaps that must be answered mainly on the importance of the reverse process that can and should be applied to all waste and not only to glass. In addition to the survey research used as part of the methodology, the methodology of bibliographic study was also used to present the theoretical framework of the work.